Quantitative gait analysis of patients with severe sacroiliac joint dysfunction: a prospective clinical study - Lodin, Jan; Jelínek, Marek; Procházka, Jan; Sameš, Martin; Vachata, Petr (Journal of neurosurgical sciences, 2023)
BACKGROUND: Sacroiliac joint (SIJ) dysfunction is a chronic painful condition responsible for up to 30% of back pain. Treatment modalities include physiotherapy, intraarticular analgesic injections, ablation techniques or SIJ fusion. The severity of SIJ dysfunction is commonly assessed via subjective pain or disability scales. Quantitative gait analysis offers an objective means of evaluating patients with SIJ dysfunction prior to its surgical treatment. METHODS: Ten patients diagnosed with severe SIJ dysfunction were matched with 10 healthy controls. All individuals underwent quantitative 3D gait analysis using the Qualisys program and statistical analysis was performed to identify significant differences in gait parameters between the two groups. RESULTS: Two groups of data were obtained; angular parameters described by the Gait Profile Score (GPS) and spatiotemporal parameters described in standard SI units. Statistically significant differences were found between the patient and control group for parameters: overall GPS (P=0.049), hip abduction/adduction (P=0.017) and ankle plantar/dorsal flexion (P=0.003), stride length (P=0.002), step length (P=0.001), swing time (P=0.03) and initial double limb support (P=0.02). CONCLUSIONS: This paper is the first to perform complex quantitative gait analysis of patients with SIJ dysfunction and to compare it with healthy individuals. These results can provide clinicians with baseline gait values for these patients to objectively quantify the extent of their disease.
Keywords: Sacroiliac Joint; Pain; analýza chůze; bolest; Gait Analysis; lidé; Spinal Diseases; prospektivní studie; Prospective Studies; nemoci páteře; sakroiliakální kloub; Humans